A comparison of methods to experimentally induce chalk brood disease in honey bees - Flores, J.M.=700 1 Gutierrez, I.; Puerta, F.
(Es, En)
ilus., 21 ref.
Keywords: APIS MELLIFERA; ASCOSPHAERA APIS; MICOSIS; ENFERMEDADES FUNGOSAS; ENSAYO; INOCULACION; ESPAÑA